Rhythmic Cilium in SCN Neuron is a Gatekeeper for the Intrinsic Circadian Clock - Hai-Qing, Tu; Sen, Li; Yu-Ling, Xu; Yu-Cheng, Zhang; Xiao-Xiao, Jian; Song Guang-Ping; Wu, Min; Zeng-Qing, Song; Hu Huai-Bin; Pei-Yao, Li; Li-Yun, Liang; Jin-Feng, Yuan; et al. (bioRxiv, 2022)
The internal circadian rhythm is controlled by the central pacemaker in the hypothalamic suprachiasmatic nucleus (SCN). SCN drives coherent and synchronized circadian oscillations via intercellular coupling, which are resistant to environmental perturbations. Here we report that primary cilium is a critical device for intercellular coupling among SCN neurons and acts as a gatekeeper to maintain the internal clock in mice. A subset of SCN neurons, namely neuromedin S-producing (NMS) neurons, exhibit cilia dynamics with a pronounced circadian rhythmicity. Genetic ablation of ciliogenesis in NMS neurons enables a rapid phase shift of the internal clock under experimental jet lag conditions. The circadian rhythms of individual neurons in cilia deficient SCN slices lose their coherence following external perturbations. Rhythmic cilia dynamics drive oscillations of Sonic Hedgehog (Shh) signaling and oscillated expressions of multiple circadian genes in SCN neurons. Genetic and chemical inactivation of Shh signaling in NMS neurons phenocopies the effect of cilia ablation. Our findings establish ciliary signaling as a novel interneuronal coupling mechanism in the SCN and may lead to novel therapy of circadian disruption-linked diseases. Competing Interest Statement The authors have declared no competing interest.